2020
DOI: 10.4269/ajtmh.19-0819
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Anodic Antigen (CAA): A Highly Sensitive Diagnostic Biomarker to Detect Active Schistosoma Infections—Improvement and Use during SCORE

Abstract: The Schistosomiasis Consortium for Operational Research and Evaluation (SCORE) was funded in 2008 to conduct research that would support country schistosomiasis control programs. As schistosomiasis prevalence decreases in many places and elimination is increasingly within reach, a sensitive and specific test to detect infection with Schistosoma mansoni and Schistosoma haematobium has become a pressing need. After obtaining broad input, SCORE supported Leiden University Medical Center (LUMC) to modify the serum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
103
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 46 publications
0
103
1
Order By: Relevance
“…These efforts are described elsewhere in this supplement. 44 In addition, because of the extreme need, SCORE also supported initial efforts to use CAA in the development of a rapid diagnostic 44 that would be suitable for mapping both S. mansoni and S. haematobium.…”
Section: Other Score Efforts Related Tomentioning
confidence: 99%
“…These efforts are described elsewhere in this supplement. 44 In addition, because of the extreme need, SCORE also supported initial efforts to use CAA in the development of a rapid diagnostic 44 that would be suitable for mapping both S. mansoni and S. haematobium.…”
Section: Other Score Efforts Related Tomentioning
confidence: 99%
“…In areas on Pemba with an apparent prevalence of < 10% by urine filtration, the prevalence determined with the UCP-LF CAA assay was almost three times higher. 3,41 Other limitations of the Zanzibar elimination study are described in a recent article on the 5-year study results. 16 The SCORE studies provide lessons learned for future research, such as the difficulty conducting randomized control trials (RCTs) to assess strategies to interrupt transmission of schistosomiasis.…”
Section: Discussionmentioning
confidence: 99%
“…SCORE's work on developing and evaluating mapping and diagnostic tools is described in other articles in this supplement. 2,3 In 2012, the World Health Assembly (WHA) issued resolution WHA 65.21, which called for the expansion of schistosomiasis control programs and to "initiate elimination campaigns where appropriate." 4 Following this, in 2013, SCORE received supplemental funding from the BMGF to build on data and experiences obtained by SCORE thus far and expand operational research on elimination of schistosomiasis.…”
Section: Introduction and Overview Of Score Portfolio In Eliminationmentioning
confidence: 99%
“…SCORE also invested substantially into the development of the highly sensitive and genus-specific UCP-LF CAA assay. 38 This tool should play an important role as a highly sensitive and specific diagnostic test and for verification of elimination of schistosomiasis. This assay has now been used many times, including in the SCORE studies within the ZEST program on Zanzibar, where it demonstrated much higher levels of S. haematobium than measured by the widely used urine filtration method.…”
Section: Contributions By Other Score Findingsmentioning
confidence: 99%
“…25 The UCP-LF CAA assay was also used in Burundi 24 and Rwanda, where it contributed to our understanding of the strengths and limitations of the POC-CCA, and in numerous other studies. 38 SCORE's role in refocusing attention on the importance of snails in transmission. SCORE has contributed substantially to a rejuvenation of interest in the control of the vector snails and the potential of monitoring snails in determining the force of infection.…”
Section: Contributions By Other Score Findingsmentioning
confidence: 99%